Monetary and Exchange Rate Policies of the Euro Area. (IMF Staff Country Reports; Country Report, 2001)
The euro area continues to perform well, owing to its sustained employment creation, rising disposable income, buoyant internal demand, and low inflation. Executive Directors agreed that favorable external developments and sound macroeconomic fundamentals had produced robust area-wide growth. They cautioned that high oil prices and a weak euro might undermine prevailing wage moderation and set in motion domestic inflation pressures. They emphasized the need to tighten monetary and fiscal policies, and accelerate structural reforms to sustain economic growth.